VALUE RELEVANCE & PREDICTIVE VALUE OF COMPREHENSIVE INCOME FROM ENTITIES LISTED IN ISE - Yessica (Journal of Business, Management, and Accounting, 2020)
After the convergence of IFRS in Indonesia, according to Statement of Financial Accounting Standards 1, economic entity are obliged to provide information about comprehensive income in their financial statement. The change of regulation is expected to increase earning quality, measured by value relevance and predictive value. The purpose of this research is to know deeper about the impact of IFRS convergence in Indonesia, especially related to the presentation of comprehensive income, to the quality of net income and comprehensive income, measured by value relevance and predictive value. Further, the value relevance and predictive value of comprehensive income will be compared to the value relevance and predictive value of net income. This research used the quantitative approach, with the sample from entities listed in Indonesia Stock Exchange in the year of 2011-2014, except for financial sector firm. The result shows that there are significant value relevance and predictive value whether for comprehensive income or net income. But, if the value relevance and predictive value of both incomes are compared, the finding show that net income is superior to net income. But it is important to note that the superiority of net income compared to comprehensive income is not significant.